PRINCIPLES AND CONTENT OF ENGLISH LANGUAGE TEACHING METHODOLOGY IN ANDRAGOGIC EDUCATION - Abdiyev Akmal Urakbayevich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article talks about the methodology of language teaching, in particular, the andragogic approach to the methodology of teaching English. The content, principles and methods of androgogic education are studied in the case of teaching English. The issue of implementing foreign methods into national methods is also highlighted.